Evaluate the efficacy of teaching programme regarding self-assessment among knee osteoarthritis patients: a cross sectional study - Shihora, Umang; Motwani, Paras (International Journal of Research in Orthopaedics, 2017)
Background: Lack of knowledge may lead to depression, anxiety and poor coping skills, which may affect the patient’s quality of life while health education is an effective intervention and can reduce pain and disability. Hence the present study was planned with the following aim to assess the knowledge regarding self-care among knee osteoarthritis patients and to develop and administer structured teaching program from knee osteoarthritis patients. Methods: Data related to the study were collected from knee osteoarthritis patients attending the out patients Department at Medical Institute at Bhuj district. The period of conduction of study was approximately one year. A total of 100 patients diagnosed with knee arthritis were included in the study. Results: respondents with an immediate family member with knee OA averaged a 5.5 higher knowledge score than respondents whose family members did not have the condition (p<0.001). Respondents diagnosed clinically of knee OA averaged 2.06 higher knowledge score in comparison to respondents without knee OA (p=0.011). Conclusions: A higher knowledge of knee OA was found for respondents with tertiary education over those with a primary or secondary education. The results from this cross-sectional study impact important public health decisions, given that respondents over 50 years, with a family history, self-awareness, and a knee OA diagnosis, showed better knowledge of symptomatic knee OA as shown in the multivariate analysis.